'On one's own strength' Healthcare providers' experience with introducing Marte Meo Counselling in dementia care. (29th July 2015) - Lykkeslet, Else; Gjengedal, Eva; Skrondal, Torill; Storjord, May‐Britt
Abstract : Aim: The aim of the present action research study was to investigate the healthcare providers' experiences with introducing Marte Meo Counselling (MMC) in a dementia‐specific care unit. Background: Research on the use of MMC shows that healthcare providers saw the patients' resources and needs more clearly and achieved increased awareness of their own skills. Design and method: An action‐oriented research including a three‐phase strategy was applied: the mapping phase, the intervention phase and the evaluation phase. During the 5‐month mapping phase, two researchers conducted participant observation of a total of 50 hours. The intervention phase consisted of lectures, clinical supervision in MMC and seven reflection groups and lasted 12 months. In the six‐month evaluation phase, participant observation of a total of 48 hours was conducted. Four focus group interviews took place during the whole study period of 2 years. Results: The staff went through a process of change described by the following themes: from challenging behaviour to challenging interaction; from generalised skills to contextualised relational care; and from personal challenges to a professional community. Conclusions: As a result of MMC, the healthcare providers realised the value of taking into account the patients' context in dementia care and of being active participants in the patients' world. The focus changed from regarding challenging behaviour as symptoms of a disorder to being a challenge to interaction. Implications for practice: Marte Meo Counselling should be combined with continuous reflection to improve healthcare providers' interaction with people who live with dementia. The reflection groups gave the caregivers an opportunity for discussions that would otherwise be impossible in their busy everyday life.